2012
DOI: 10.1002/jssc.201200165
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of acrylate monolith using photopolymerization: Effect of light intensity on electrochromatographic performance

Abstract: Figure 1 was represented in an unclear format. See below for a larger and better readable version of Figure 1: Figure 1. Influence of light intensity P and irradiation time t (or irradiation energy W) on minimal plate height H min (m) for fluoranthene. C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The performances of HA‐filled COC microchips for the reversed‐phase separation of six PAH (anthracene, fluoranthene, pyrene, benzo‐a‐anthracene, benzo‐a‐pyrene, and benzo‐k‐fluoranthene) were characterized elsewhere . It was shown that, with a mobile phase containing 70% ACN, the retention factors of solutes were contained between 5.2 and 17.8 and efficiencies ranged from 200 000 to 250 000 plates/m at a linear velocity of 1.6 mm/s for a separation length of 2 cm (the corresponding time analysis was 3.5 min).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The performances of HA‐filled COC microchips for the reversed‐phase separation of six PAH (anthracene, fluoranthene, pyrene, benzo‐a‐anthracene, benzo‐a‐pyrene, and benzo‐k‐fluoranthene) were characterized elsewhere . It was shown that, with a mobile phase containing 70% ACN, the retention factors of solutes were contained between 5.2 and 17.8 and efficiencies ranged from 200 000 to 250 000 plates/m at a linear velocity of 1.6 mm/s for a separation length of 2 cm (the corresponding time analysis was 3.5 min).…”
Section: Resultsmentioning
confidence: 99%
“…The monolith based on HA and BDDA monomers, was previously used in COC electrochromatographic microchips . The porogenic mixture made of 54% w/w of ACN, 23% w/w of ethanol, and 23% w/w of water, is dissolved in the monomer mixture containing 66.4% w/w of HA and 33.6% w/w of BDDA, with the monomerto porogens ratio equal to 34.5:65.5 w/w.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations